1966
DOI: 10.1002/rds196613257
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Frequency Changes in Radio Waves Propagating Through a Moving Ionosphere

Abstract: Doppler frequency changes for a vertically incident and reflected radio wave caused by a redistribution of electrons in the ionosphere due to drift motions set up by an electric field across the earth's main magnetic field are discussed. The Doppler frequency change is given as a linear function of the two horizontal components of the electric field with coefficients which are functions of the relevant ionospheric parameters and the frequency of the sounding radio wave. The Doppler frequency. change can also b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

1969
1969
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 17 publications
1
43
0
Order By: Relevance
“…The ®rst attempts to model the coupling of geomagnetic ®eld¯uctuations to the ionospheric plasma were by Rishbeth and Garriott (1964) and Jacobs and Watanabe (1966). Poole et al (1988) showed that for downgoing transverse Alfve n mode waves three mechanisms contribute to the ionospheric Doppler oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…The ®rst attempts to model the coupling of geomagnetic ®eld¯uctuations to the ionospheric plasma were by Rishbeth and Garriott (1964) and Jacobs and Watanabe (1966). Poole et al (1988) showed that for downgoing transverse Alfve n mode waves three mechanisms contribute to the ionospheric Doppler oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the correlation between the amplitudes of the positive spike and the amplitude of the SC reported by HUANG et al (1973) has not been noticed in our data. It is to be emphasized that our results pertain to observations over two long radio propagation paths of different lengths (1290km and 5700km) while HUANG et al (1973) used data for one short propagation path JACOBS and WATANABE (1966) theoretically investigated the relation between Doppler frequency changes and sudden commencements for vertically insident and reflected radio waves. A comparison of our results with those predicted by JACOBS and WATANABE (1966) using the equivalence theorem for frequency deviations could not be made due to lack of electron density profile data necessary to fix the angle of fire using ray tracing procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Fenwick and Villard (1960) ®rst suggested that changes in the Earth's magnetic ®eld were associated with observed shifts in the frequency of HF radio signals. Since then, short period oscillations of HF wave signal frequency have been correlated with magnetospheric ULF pulsations (which have periods in the range 0.1 s to 600 s) measured by ground magnetometers (e.g Jacobs and Watanabe, 1966;Klostermeyer and RoÈ ttger, 1976;Menk, 1992). For a more detailed description of the Doppler technique see Georges (1967) and for a discussion on its application to observing ULF waves see Wright et al (1997).…”
Section: The High-latitude Doppler Soundermentioning
confidence: 99%